Pembiayaan Berbasis Jual Beli dan Kinerja Bank Umum Syariah di Indonesia - Puspasari, Oktaviani Rita (Jurnal Riset Keuangan dan Akuntansi, 2016)
This study examine how trade basis financing products which are : murabahah and istishna has an effect to the Islamic Bank performance in Indonesia which meassured by profitability, then the profitability proxied by ROA (return on asset). The sample selection method is purposive sampling and obtained eleven Islamic bank in 5 years period observation with 53 data are being sampled. Multiple regression analysis is used to analyze the data. The results shows that volume of murabahah financing product has negative effect also has no signifficant effect to Islamic Bank performances, istishna’ financing has positive and significant effect to the Islamic bank performance in Indonesia, while salam financing have no balance anymore on the total Islamic Bank financing with many internal and external factors which affected, as well as trade basis financing products has no significant effect to the Islamic Bank Performance.